Resoluções de equações diferenciais ordinárias por séries de potências - Kutz, Felipe de Jesus (2017)
In this work I study solutions of Second Order Linear Diferential Equations with non-constant coefficients. In order to solve these kinds of problems I use power series methods, in particular the Sucessive Differentiations method. Also I studied the Frobenius method and its cases. Finally I studied an alternative application of Sucessive Differentiations method for non-homogeneus equations. I compared the obtained results with known methods in order to get consistent results. This work also has a proof of the convergence of alternative Sucessive Differentiations method based in Theorem of the Strong Operator Convergence.